2021
DOI: 10.1007/s12011-021-02795-y
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Copper Administration at the Beginning of a Fixed-Time Artificial Insemination Protocol in Beef Cattle: Effect on Ovarian Function and Pregnancy Rates

Abstract: The aim of this study was to evaluate the association between plasma copper (Cu) concentration and ovarian function during a fixed-time artificial insemination (FTAI) protocol and the effect of parenteral Cu administration (100 mg) at the start of such protocol (day 0) on area of preovulatory follicle (APF); area of corpus luteum (ACL), plasma estradiol (E2), and progesterone (P4) concentrations; CL blood flow (CLBF); and pregnancy rate in beef heifers and cows. In cows, plasma Cu concentration on days 0 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that the ovarian activity in ruminants is affected by mineral deficiency (Yatoo et al 2013), particularly Cu, for its role in reproduction. This element has been reported as the second most widespread mineral deficiency that affects grazing globally (Anchordoquy et al 2021). Pregnancy is associated with an increase of plasma Cu as serum ceruloplasmin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ovarian activity in ruminants is affected by mineral deficiency (Yatoo et al 2013), particularly Cu, for its role in reproduction. This element has been reported as the second most widespread mineral deficiency that affects grazing globally (Anchordoquy et al 2021). Pregnancy is associated with an increase of plasma Cu as serum ceruloplasmin.…”
Section: Introductionmentioning
confidence: 99%